Youth Engagement for Agroecology: An Application of Photo-Voice Methodology in the Tunisian Agroecological Living Landscape – A Case Study from the Community of Kesra - Idoudi, Zied; Frija, Aymen; Alary, Veronique; Tebourbi, Ons; Bessouda, Balkiss; Kortas, Ghada; Shijagurumayum, Meghajit; Djurfeldt, Nadia; Rietveld, Anne (International Center for Agricultural Research in the Dry Areas, 2024)
Photo-Voice is a participatory research method that empowers individuals, typically marginalized or underrepresented groups, to use photography and storytelling to express their experiences, perspectives, and aspirations. The goal of using photo voice in this study is to engage young women and men in documenting and sharing their views on rural livelihoods, agriculture, and agroecology. Through photo voice, participants can highlight their opportunities, challenges, needs and aspirations related to these issues. It also aims to facilitate youth engagement in stakeholder discussions, elevate their concerns, and foster cross-cultural connections and learning through social media platforms. Ultimately, the goal is to generate actionable insights that address the underrepresentation of young women and men in farmers' collective action groups and agriculture, and to inform stakeholders.